THE ROLE OF CAPITAL ADEQUACY RATIO (CAR) IN CONTROLLING LIQUIDITY RISK AND CREDIT RISK, SO ABOUT PROFITABILITY IMPROVEMENTS - Probowati, Lina; Nabhan, Faqih (Fakultas Ekonomi dan Bisnis Islam, 2021)
Abstract This study aims to determine the effect of capital adequacy ratio (CAR) on profitability. This research was conducted on a sample of 10 Islamic Commercial Banks registered with the Financial Services Authority (OJK) in the 2010-2020 period. This study uses path analysis with SPSS 26 application. The results of this study indicate that CAR is not able to directly increase profitability, but CAR has a negative effect on liquidity risk and credit risk. This study also found that credit risk has a negative effect on Profitability, but Liquidity Risk has no effect on Profitability.Keywords: Capital Adequacy Ratio, Liquidity Risk, Profitability